Growth Performance of Hill Dipterocarp Forests Five Years after Harvesting at the Angsi Forest Reserve, Negeri Sembilan, Malaysia, 2007 - Nobilly, Frisco (2007)
The future long-term timber supply from sustainably managed forest in Peninsular Malaysia is largely dependent on the availability of timber from the productive Permanent Forest Estate (PFE) especially from the Hill Dipterocarp Forests. Future log supply also will come from the second and successive harvest in logged-over forest. Specific information on behaviours of particular forest stand pertaining to growth performance, mortality, density, structure and species composition is required to evaluate the management systems and its suitability under different forests types. The study was conducted in a logged over Hill Dipterocarps Forest in Angsi Forest Reserve, Negeri Sembilan with the objective to evaluate the growth response five years after harvesting. The data consist of five annual measurements (2000-05) collected from four I-ha permanent sample plots. The data were analysed in terms of diameter increments, basal areas, tree volumes and also growth projection using existing growth and yield model. The results show pattern and trend of tree growth five years after logging. The stocking of trees, basal area and volume for both trees over 5 and 30 cm dbh were significantly -different ( ~ ~ 0 . 0 5a)m ong plots, species groups and measurement years. The ANOVA also showed that the interaction between species groups, study plots and measurement years were also significant (~~0.05). Stocking of trees for both over 5 and 30 cm dbh showed an increment over the measurement period. However, the overall increment rates of all trees over 30 cm dbh were relatively low, when compared to the rates assumed under the Selective Management System (SMS). The overall diameter periodic annual increment (DPAI) of 0.65 cm tree-' yr-' for all trees over 30 cm dbh is considerably lower than the rate of 0.8 to 1.0 cm tree-' yr-' assumed under the SMS. Although the DPAI of the dipterocarps was higher than the non-dipterocarps, their overall contributions to forest growth was small due to their lower stocking in the residual stand. The overall mean annual mortality (3.51%) of all trees over 30 cm dbh for 5-year period was higher than that assumed under the SMS (0.9%). Based on these growth rates, anticipating a second cut in 25 to 30 years as stipulated under SMS, would not be applicable for this area. Therefore, future research on behaviour of the forest should be conducted. Based on projection of growth and yield model until year 60 indicates that growth in timber, basal area and the number of stems per hectare is increasing each period until end of the projection period (year 60) at slower state. This shows that the study areas will experience long growth period due to high density of trees in lower diameter class.